Sputtered crystalline TiO2 film drives improved surface properties of titanium-based biomedical implants - Pantaroto, Heloisa Navarro; Cordeiro, Jairo Matozinho; Pereira, Lucas Toniolo; de Almeida, Amanda Bandeira; Nociti Junior, Francisco Humberto; Rangel, Elidiane Cipriano [UNESP]; Azevedo Neto, Nilton Francelosi [UNESP]; da Silva, Jose Humberto Dias [UNESP]; Barão, Valentim Adelino Ricardo (Elsevier, 2021)
Different crystalline phases in sputtered TiO2 films were tailored to determine their surface and electrochemical properties, protein adsorption and apatite layer formation on titanium-based implant material. Deposition conditions of two TiO2 crystalline phases (anatase and rutile) were established and then grown on commercially pure titanium (cpTi) by magnetron sputtering to obtain the following groups: A-TiO2 (anatase), M-TiO2 (anatase and rutile mixture), R-TiO2 (rutile). Non-treated commercially pure titanium (cpTi) was used as a control. Surfaces characterization included: chemical composition, topography, crystalline phase and surface free energy (SFE). Electrochemical tests were conducted using simulated body fluid (SBF). Albumin adsorption was measured by bicinchoninic acid method. Hydroxyapatite (HA) precipitation was evaluated after 28 days of immersion in SBF. MC3T3-E1 cell adhesion, morphology and spreading onto the experimental surfaces were evaluated by scanning electron microscopy. Sputtering treatment modified cpTi topography by increasing its surface roughness. CpTi and M-TiO2 groups presented the greatest SFE. In general, TiO2 films displayed improved electrochemical behavior compared to cpTi, with M-TiO2 featuring the highest polarization resistance. Rutile phase exhibited a greater influence on decreasing the current density and corrosion rate, while the presence of a bi-phasic polycrystalline condition displayed a more stable passive behavior. M-TiO2 featured increased albumin adsorption. HA morphology was dependent on the crystalline phase, being more evident in the bi-phasic group. Furthermore, M-TiO2 displayed normal cell adhesion and morphology. The combination of anatase and rutile structures to generate TiO2 films is a promising strategy to improve biomedical implants properties including greater corrosion protection, higher protein adsorption, bioactivity and non-cytotoxicity effect.
Keywords: Blood proteins; Corrosion; Dental implants; Hydroxyapatites; Magnetron sputtering; Titanium